The Implementation of Project-Based Learning Model – PJBL To Increase The Poetry Writing Results On Poetry Study Course in Indonesian Literature of Teacher Training and Education Faculty Universitas Jambi - Liza Septa Wilyanti; Julisah Izar; Nurfitri Susanti (Bahterasia : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
This reasearch aimed to increase the students poetry writing results onPoetry Study Course in Indonesian Literature of Teacher Training andEducation Faculty Universitas Jambi by using Project-based learningmodel (PBJL). The methodology of this research was the classroomaction approach by using project-based learning model (PBJL) whichemphasized the students activities to produce the products and used theprojects/activities as a learning process to reach the attitude competition,knowledge, and skills. The results of this research showed that theapplication of this project-based learning process (PBJL) could increasethe students poetry writing results. Based on the results of projectworksheets, the average score on the project worksheet was 72,50 whilethe learning success target was 70,00. So, the success target of learningresults on cycle 1 was achieved and could be continued to the next cyclesin order to get the students learning score results which could be reached80 or could be categorized into A. The students poetry writing results inIndonesian Literature could increase after using project-based learningmodel (PBJL).Keywords: Project-based learning model (PJBL), Poetry Writing,Poetry Study Course